Spiritual Guide Light Of The Nation - Ubaydullaeva, Saodat (The journal of contemporary issues in business and government, 2021)
Some aspects of multidimensional oeuvre of one of the prominent representatives of Uzbek national literature, scientific and public figure, an outstanding scientist-literature scholar, translator and publicist, Uzbekistan hero Ozod Sharafiddinov are discussed in this article. Special attention paid to his works, which focus on social and political life of the country, in particular, issues on religion, language, spirituality and thinking, culture of lection and other issues, as well as his translations of unique pieces of work of the world literature. The article entails specific features of the scientists’ works, his individual style, critical perspectives and best practices of translation. Special attention is given to the publicity of Ozod Shafafiddinov, where pertinent issues of country’s social life are reflected. Confessions of the fellow men as well as students about the talented scientist are given in the article.